Determinants of audit report lag: evidence from Indonesia's basic materials sector (2019-2022) - Conidia Asih Prastiwi; Ajeng Luthfiyatul Farida (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Companies registered on the Indonesia Stock Exchange (IDX) must present financial reports in accordance with accounting standards and be audited by an independent auditor in a timely manner. This study examines the influence of leverage, financial distress, tax risk, and earnings volatility on audit report lag in the basic materials sector companies listed on the IDX for 2019-2022. Using purposive sampling techniques, the study obtained 19 samples from an initial population of 26 companies after eliminating outliers and analyzed the data using panel data regression through Eviews 12 software. The results show that leverage and financial distress have no significant effect on ARL, indicating that these factors do not directly affect the time taken to complete the audit process for companies in the basic materials sector. However, earnings volatility is shown to have a significant negative effect on ARL, indicating that companies with greater earnings fluctuations tend to take longer to complete the audit of their financial statements. This study contributes to the understanding of the factors that influence ARL in the basic materials sector in Indonesia and can serve as a basis for further research on the influence of external and internal factors on corporate financial reporting transparency.